Comparative efficacy of face-to-face and internet-based cognitive behavior therapy for generalized anxiety disorder: A meta-analysis of randomized controlled trial - Zhang, Wenle; Du, Yun; Yang, Xiangyun; Wang, Encong; Fang, Jiexin; Liu, Ziqi; Wu, Shanqian; Liu, Qinqin; Hu, Yongdong (Frontiers in Psychiatry, 2022)
Objective: The study aimed to examine the available evidence for face-to-face cognitive behavior therapy (CBT) and internet-based cognitive behavior therapy (ICBT) to ascertain the comparative efficacy of these two forms on reducing anxiety scores of scales in patients with generalized anxiety disorder (GAD). Moreover, due to the quarantine policy and the requirement of social distance, this study also tried to figure out whether ICBT could gain similar benefits as CBT for GAD patients during coronavivirus disease 2019 (COVID-19). Methods: This meta-analysis was registered with the International Prospective Register of Systematic Reviews (PROSPERO) according to the guidelines in the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement (registration number CRD42021241938). Therefore, this study conducted a meta-analysis of randomized controlled trials (RCTs) examining CBT or ICBT to treat GAD patients diagnosed by DMS-IV. The researchers searched PubMed, MEDLINE, Embase, PsycINFO, and the Cochrane Database of Systematic Reviews for relevant studies published from 2000 to May 9, 2021. Evidence from RCTs was synthesized by Review Manager 5.4 as standardized mean difference (SMD) for change in scores of scales via random-effects meta-analysis. Results: Twenty trials representing 1433 participants were pooled. ICBT, relative to CBT, demonstrated a more significant change in scales (SMD=-0.18 vs SMD=-0.03), and after removed studies with active control, ICBT still showed a better response (SMD=-0.26 vs SMD=-0.18). Conclusion: For the treatment of GAD, ICBT works more efficaciously than CBT and can be CBT's candidate substitute, especially in the COVID-19 pandemic era, given the fact that the internet plays a crucial role in dealing with social space constraints.